TEACHER'S MANAGEMENT OF THE EDUCATIONAL PROCESS BASED ON CREATIVE APPROACH (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article is devoted to opinions on the nature of creativity, teachers and how their creativity is manifested during activities, and the impact of the teacher's creative approach to the development of children.